Treatment of vegetable oil industry wastewater and bioelectricity generation using microbial fuel cell via modification and surface area expansion of electrodes. Issue 4 (4th January 2023) - Yaghmaeian, Kamyar; Rajabizadeh, Ahmad; Jaberi Ansari, Farshid; Puig, Sebastià; Sajjadipoya, Roohallah; Baghani, Abbas Norouzian; Khanjani, Narges; Mansoorian, Hossein Jafari
Abstract: BACKGROUND: This study evaluates the treatment of vegetable oil industry wastewater using dual‐chamber microbial fuel cells (MFCs) via modification and surface area expansion of cost‐effective electrodes. The modified electrodes were applied as both the anode and cathode to investigate their treatment capacity and electrochemical performance. Carbon paper anodes were modified using TiO2 ‐HX@MWCNT‐COOH‐Al2 O3 composite. Activated carbon powders originating from Bambuseae were used as the low‐cost catalyst for the carbon felt cathode. The synthesized catalysts were characterized by Field‐Emission Scanning Electron Microscope (FE‐SEM), Energy Dispersive X‐ray Spectroscopy (EDX), and Brunauer–Emmett–Teller (BET) techniques. The electrochemical properties of the MFCs were investigated by Electrochemical Impedance Spectroscopy (EIS). RESULTS: The highest average removal efficiencies of COD (chemical oxygen demand), BOD5 (5‐day biochemical oxygen demand), NH4 + (ammonium), NH3 − (nitrate), TSS (total suspended solids), and VSS (volatile suspended solids) were 94 ± 3% (33 kgCODrem /m 3 .d), 89 ± 1% (12 kgBODrem /m 3 .d), 87 ± 1% (0.24 kgNH4 + ‐Nrem /m 3 .d), 74 ± 3% (0.05 kgNO3 − ‐N/m 3 .d), 79 ± 2% (1 kgCODrem /m 3 .d), and 65 ± 3% (0.73 kgCODrem /m 3 .d), respectively. The highest average power density of 30 ± 5 W/m 3 was obtained when treating vegetable oil industry wastewater. The highest average coulombic efficiency (CE) of 85 ± 3% and energy efficiency (EE) of 35 ± 2% were achieved. The EIS results showed that the high conductivity and large unique surface area significantly enhanced the charge transfer efficiency on the electrode surface. CONCLUSION: The results indicated that the TiO2 ‐HX@MWCNT‐COOH‐Al2 O3 composite can be used to reinforce the performance of MFCs. © 2022 Society of Chemical Industry (SCI). Abstract :